Measuring Gastric pH in Tube-fed Children With Neurologic Impairments and Gastroesophageal Disease. Issue 6 (June 2021) - Tjon, James; Cooper, Mitchell; Pe, Michael; Boodhan, Sabrina; Mahant, Sanjay; Avitzur, Yaron; Atenafu, Eshetu G.; Moradipour, Tassnim; Sepiashvili, Lusia; Cohen, Eyal
ABSTRACT: Objectives: The aim of the study was to determine the extent of agreement between pH paper and handheld pH meter with a laboratory pH meter for gastric pH measurement in children with neurologic impairments and gastrostomy tubes who have gastroesophageal reflux disease (GERD). Methods: In this prospective observational study, gastric contents were aspirated from gastric or nasogastric tubes and the pH measured using 3 techniques: pH paper, handheld pH meter, and laboratory pH meter (the gold standard). Agreement between techniques was assessed with intraclass correlation coefficient (ICC), Bland-Altman analysis, and kappa statistic. Results: Among 43 patients contributing 67 gastric samples, the ICC was 0.75 (95% confidence interval [CI]: 0.69–0.97) between the handheld and laboratory meters, 0.69 (95% CI: 0.63--0.94) between the pH paper and laboratory meter and 0.69 (95% CI: 0.63–0.94) between the handheld meter and paper. The Bland-Altman analysis between the handheld and lab meters showed a mean difference of −0.03 pH units (limits of agreement: −0.52 to 0.47 pH units) and 0.17 pH units (limits of agreement: −0.99 to 1.33 pH units) between the paper and lab meter. The kappa coefficients for a pH ≥4 were 1.0 (95% CI: 1.0--1.0) between the handheld and lab meters and 0.9 (95% CI: 0.77--1.0) between the paper and lab meter. Conclusions: The findings suggest that both point-of-care tests, the pH meter and pH paper, correlate well with the gold standard for testing pH with a laboratory pH meter, indicating usefulness in point-of-care testing for monitoring gastric pH in tube-fed children with neurologic impairments and GERD.